2009
DOI: 10.1213/ane.0b013e318199dc72
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement: First International Workshop on Anesthetics and Alzheimer’s Disease

Abstract: In order to review the current status of the potential relationship between anesthesia and Alzheimer's disease, a group of scientists recently met in Philadelphia for a full day of presentations and discussions. This special article represents a consensus view on the possible link between Alzheimer's disease and anesthesia and the steps required to test this more definitively.There is growing interest in the potential relationship between anesthesia and the onset and progression of neurodegenerative disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 33 publications
(34 reference statements)
0
72
0
Order By: Relevance
“…Few attempts have been made to relate POCD or PreCI to the onset of dementia in the longer term. This is unfortunate because recent animal studies suggest an association between cognitive change after anesthesia and the pathophysiology of AD 10,34 ; however, this link has not been shown in clinical studies. The wealth of data outlining the progression of aMCI to dementia in population studies cannot be applied to PreCI because of the discrepancy in definitions between the two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Few attempts have been made to relate POCD or PreCI to the onset of dementia in the longer term. This is unfortunate because recent animal studies suggest an association between cognitive change after anesthesia and the pathophysiology of AD 10,34 ; however, this link has not been shown in clinical studies. The wealth of data outlining the progression of aMCI to dementia in population studies cannot be applied to PreCI because of the discrepancy in definitions between the two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus statement of the First International Workshop on Anesthetics and Alzheimer's Disease 22 concluded that ‘there is sufficient evidence at multiple levels to warrant further and more definitive investigations of the onset and progression of Alzheimer's disease and neurodegeneration after anesthesia and surgery’. We therefore undertook a longitudinal cohort study of cognitive function in patients and controls from the Oxford Project to Investigate Memory and Ageing (OPTIMA), who were followed with frequent cognitive assessments and records of episodes of anaesthesia for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This opinion has been emphasized in the fields of both AD and anesthesia research. 4 The commonly used inhalation anesthetic isoflurane has been shown to induce caspase activation and apoptosis, and to increase β-amyloid protein (Aβ) oligomerization and accumulation in vitro and in vivo. [5][6][7][8][9][10][11][12][13] Desflurane, another commonly used inhalation anesthetic, may not induce these detrimental effects in cultured cells.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%